Influence of elevated Zn (II) on Anammox system: Microbial variation and zinc tolerance - Zhang, Xiaojing; Chen, Zhao; Ma, Yongpeng; Zhou, Yue; Zhao, Siyu; Wang, Lina; Zhai, Hanfei (Bioresource technology, 2018)
•Zinc ion performed significant inhibition on Anammox process.•AAOB had self-adaption to elevated Zn (II) in 1–10 mg L−1.•The irreversible suppression threshold on AAOB was 20 mg L−1 Zn (II).•Zn (II) addition led to the biodiversity increase of Anammox system.•Relative abundance of AAOB significantly rebounded after long-term acclimatization. Nitrogen removal by anaerobic ammonium oxidation (Anammox) has attracted increasing attention in nowadays. An Anammox biofilter was subjected to a continuous loading of elevated Zn (II). The influence of Zn (II) on the nitrogen removal, microbial community and biofilm property was investigated in the condition of 23–26 °C and 3.5 h HRT. The nitrogen removal greatly decreased to 0.054 from the initial 0.502 kg m−3 d−1, with the Zn (II) addition. Anaerobic ammonia-oxidizing bacteria (AAOB) had self-adaption to Zn (II) in 1–10 mg L−1 and was significantly enhanced after long-term acclimatization, while the suppression threshold was 20 mg L−1. Soluble microbial products (SMP) increased correspondingly with Zn (II), while extracellular polymeric substance (EPS) climbed up initially and then decreased. Anammox biofilm performed the highest zinc adsorption as 158.27 mg g−1 SS in biofilm. High Zn (II) improved the microbial diversity and lowered the Candidatus Kuenenia abuandance to 1.38% from 20.89%.